Endometrial ablation as a safe treatment for adenomyosis-related abnormal uterine bleeding in women with cerebral infarction: a case report - Zheng, Limei; Zhang, Hong; Fang, Wei; Yang, Jianhua (Frontiers in Medicine, 2025)
BackgroundAdenomyosis is often associated with abnormal uterine bleeding (AUB), which can lead to anemia. Recurrent bleeding, especially in the presence of cerebral infarction risk, may exacerbate the likelihood of cerebral infarction through a hypercoagulable state. Although the relationship between adenomyosis and ischemic stroke is less frequently explored, controlling AUB and maintaining antithrombotic therapy remain clinical challenges. This report presents the application of endometrial ablation in a patient with adenomyosis, AUB, and cerebral infarction.MethodsWe report a case of a 50-year-old female patient who developed acute ischemic stroke due to adenomyosis-related AUB. During the acute phase, the patient underwent endometrial ablation, successfully controlling the bleeding while continuing antiplatelet therapy.ResultsAfter endometrial ablation, the patient's abnormal uterine bleeding was effectively controlled, with no recurrence of cerebral infarction. At a 37-month follow-up, the patient had no further vaginal bleeding or recurrence of cerebral infarction.ConclusionThis case is the first to report the use of endometrial ablation in a patient with adenomyosis and cerebral infarction, demonstrating the potential of this procedure in emergency hemostasis and maintaining antithrombotic therapy. Endometrial ablation is an effective, minimally invasive treatment with a quick recovery, making it a viable option for patients who cannot tolerate major surgery.